Performance of MPPT-Based Minimum Phase Bipolar Converter for Photovoltaic Systems - Kumar P.; Singh R.K.; Mahanty R. (My University, 2025)
The change in environmental conditions and dynamic loading distort the smooth and stable MPPT operation. Conventionally, boost and boost-derived converters are used for MPPT operations, which inherently display right half plane zero (RHPZ). The presence of RHPZ causes a transient undershoot and overshoot in the output voltages. A tradeoff between bandwidth and stability is another issue with such converters. In order to address these issues, a minimum-phase bipolar converter (MPBC) is proposed to facilitate the MPPT operation. The MPBC is derived by combining the Ćuk and SEPIC converters with some circuit modifications in both of them. These circuit modifications eliminate RHPZ from the proposed MPBC. Due to the minimum-phase behavior, the proposed MPBC can achieve high bandwidth with improved phase margin, which is required for the fast and stable MPPT operation. MPBC can operate at the high load current and provides wide operating ranges for the MPPT operation due to its buck and boost capabilities. The transient analysis of the proposed MPBC is carried out to compare its performance with the conventional bipolar converter. A 600-W scaled-down laboratory prototype is developed and implemented using Texas Instrument TMS320F28335 processor to validate the performance of the MPBC for photovoltaic systems. © 1986-2012 IEEE.